2018
DOI: 10.1002/cbdv.201800059
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of a Series of Novel Celastrol Derivatives with Amino Acid Chain

Abstract: The synthesis of celastrol analogues containing amino acid ester at the C(29) position and their evaluation for cytotoxic activities in vitro were reported. The MTT test showed that a set of derivatives with lower IC values than that of the positive control group cisplatin and the parent compound celastrol, which exhibited greater antiproliferative activities. The most potent title compounds 2a and 2e exhibited cytotoxic activities in vitro against HeLa and A549 cell lines with IC values of 0.371 and 0.237 μm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Compounds 146 and 150 showed potent antiproliferation effects. Moreover, Compound 150 showed 10‐fold stronger effect than celastrol in A549 cells, with an IC 50 value of 0.109 µm 90 . In another study, the researchers found that celastrol conjugated with glucosamine is more secure than celastrol in acute renal injury treatment 91 .…”
Section: Chemical Synthesis and Structural Modificationsmentioning
confidence: 98%
“…Compounds 146 and 150 showed potent antiproliferation effects. Moreover, Compound 150 showed 10‐fold stronger effect than celastrol in A549 cells, with an IC 50 value of 0.109 µm 90 . In another study, the researchers found that celastrol conjugated with glucosamine is more secure than celastrol in acute renal injury treatment 91 .…”
Section: Chemical Synthesis and Structural Modificationsmentioning
confidence: 98%
“…Besides, compounds (6) and (7) have a strong antiproliferative activity of Hela and A549 cell lines, which are 5 and 10 times that of celastrol (Zhang H.-J. et al, 2018;Pang et al, 2018;Wang G. et al, 2019). On the other hand, the water solubility of compound (8) is 35 times that of celastrol and its tumor suppressive activity is higher than celastrol against the PANC-1 cell line and the human lung cancer (paclitaxelresistant) A549 cell line (Jiang et al, 2016).…”
Section: Increase Solubility To Enhance Antitumor Effectsmentioning
confidence: 99%
“…In the series of amino acid derivatives, compound 99 showed the highest anticancer activity against AGS cell lines (IC 50 = 0.44 μM) and showed better anticancer activity against HCT-116, BEL-7402, and HepG-2 cell lines than the other compounds. Eight novel celastrol amino acid derivatives were synthesized, which displayed strong cytotoxic activities against A549, HeLa, and HepG-2 cell lines (Pang et al, 2018 ). In particular, the cytotoxicities of 100 and 101 against HeLa and A549 cells with IC 50 values ranging from 0.109 to 0.371 μM, the effect of cytotoxic activity was remarkably stronger than that of celastrol and cisplatin.…”
Section: Application Of Amino Acids In the Structural Modification Of Natural Productsmentioning
confidence: 99%